2016
DOI: 10.3389/fpls.2016.00430
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Inositol Biosynthesis and Nitric Oxide in the Mediation of UV-B Induced Oxidative Stress

Abstract: The involvement of NO-signaling in ultraviolet B (UV-B) induced oxidative stress (OS) in plants is an open question. Inositol biosynthesis contributes to numerous cellular functions, including the regulation of plants tolerance to stress. This work reveals the involvement of inositol-3-phosphate synthase 1 (IPS1), a key enzyme for biosynthesis of myo-inositol and its derivatives, in the response to NO-dependent OS in Arabidopsis. Homozygous mutants deficient for IPS1 (atips1) and wild-type plants were transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 65 publications
0
18
0
1
Order By: Relevance
“…Furthermore, in the model plant Arabidopsis, involvement of myo-inositol metabolism with PCD and basal immunity is well demonstrated. Reduced levels of inositol can induce severe cell death and disease symptoms by suppressing/knockdown of inositol-3-phosphate synthase [ 47 ] and myo-inositol-1-phosphate synthase [ 46 ]. Wild type phenotype can be restored by feeding these inositol deficient mutants or transgenics with inositol/galactinol [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the model plant Arabidopsis, involvement of myo-inositol metabolism with PCD and basal immunity is well demonstrated. Reduced levels of inositol can induce severe cell death and disease symptoms by suppressing/knockdown of inositol-3-phosphate synthase [ 47 ] and myo-inositol-1-phosphate synthase [ 46 ]. Wild type phenotype can be restored by feeding these inositol deficient mutants or transgenics with inositol/galactinol [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have demonstrated that plant α‐tubulin can undergo posttranslational tyrosine nitration that might be one of the hallmarks of the increased microtubular dynamics (Blume et al, ). It was also found that NO and inositol signaling pathways in plant cells can be involved in UV‐B‐triggered oxidative stress (Lytvyn et al, ). Influence of low temperatures on AFs organization in plant cells and NO involvement into this process as a signaling molecule have been not previously studied.…”
Section: Introductionmentioning
confidence: 99%
“…Hideg et al, 2013) including the activation of mitogen-activated protein kinase phosphatases (Besteiro and Ulm, 2013). UV-B mediated ROS production has also been linked with nitric oxide (NO) signalling (Lytvyn et al, 2016). UV-B induced NO has been linked with changes in microtubuli organisation (Krasylenko et al, 2012), which in turn can affect morphology though regulation of cell division, cell elongation and initiation of lateral growth.…”
Section: Stress Mediated Control Of Plant Architecturementioning
confidence: 99%